ANALISIS PERKEMBANGAN BISNIS SKINCARE DENGAN MENGGUNAKAN LIVE STREAMING TIKTOK SEBAGAI MEDIA PROMOSI (Studi Pada Brand Skincare Lokal Alldays) - Salsabila, Febrinanda; Fitria, Shoimatul (Diponegoro Journal of Management, 2023)
ABSTRACT The development of new technology and innovation in business practices causes competition for each company to become increasingly fierce. Alldays is a creative economy business operating in the beauty industry. This research aims to analyze and develop a conceptual model regarding marketing strategies using TikTok live streaming as a promotional medium to improve the performance of the Alldays beauty business as measured by the level of existence and income. In conducting this research, data was collected from the source that was the research object, namely Alldays. This research uses a qualitative research method with a case study approach. The type of case study used is Case Study Research because research is carried out on specific objects in real-life contexts contained in Alldays, which are temporary and specific. This research involves direct contact with the research object, namely Alldays, which means it is specific. The research results show that promotional activities using TikTok live streaming positively impact Alldays, especially in terms of brand awareness and e-trust. In line with this, promotional content via TikTok live streaming positively and significantly impacts purchase decisions. The marketing strategy using TikTok live streaming has positively and significantly impacted Alldays' business performance, especially in increasing existence and revenue. The continued increase in followers on social media and financial report records proves this. This research is expected to help develop the Alldays company marketing strategy and can become valuable literature for scientists.